Simultaneous Dataset of Brain, Eye and Hand during Visuomotor Tasks - Hao Zhang; Yiqing Hu; Yang Li; Shuangyu Zhang; XiaoLi Li; Chenguang Zhao (Scientific Data)
Abstract Visuomotor integration is a complex skill set encompassing many fundamental abilities, such as visual search, attention monitoring, and motor control. To explore the dynamic interplay between visual inputs and motor outputs, it is necessary to simultaneously record multiple brain activities with high temporal and spatial resolution, as well as to record implicit and explicit behaviors. However, there is a lack of public datasets that provide simultaneous multiple modalities during a visual-motor task. Functional near-infrared spectroscopy and electroencephalography to record brain activity simultaneously facilitate more precise capture of the complex visuomotor of brain mechanisms. Additionally, by employing a combined eye movement and manual response, it is possible to fully evaluate the effects of visuomotor outputs from implicit and explicit dimensions. We recorded whole-brain EEG (34 electrodes) and fNIRS (44 channels) covering the frontal and parietal cortex along with eye movements, behavior sampling, and operant behavior. The dataset underwent rigorous synchronization, quality control to highlight the effectiveness of our experiments and to demonstrate the high quality of our multimodal data framework.